Vivipary and pseudovivipary in the Poaceae, including the first record of pseudovivipary in Digitaria (Panicoideae: Paniceae) - Vega, Andrea Susana (2006)
This paper reviews and adds information about the phenomena of vivipary and pseudovivipary in the Poaceae, which are reported from 21 genera belonging to subfamilies Pooideae, Panicoideae and Chloridoideae. A previously overlooked description of pseudovivipary in Digitaria angolensis is confirmed and constitutes the first record of pseudovivipary in the genus Digitaria. This species is illustrated for the first time and the proliferation phenomenon in the spikelets is described and documented.